PEMANFAATAN MEDIA SOSIAL UNTUK PROMOSI UMKM PEMBUATAN POT TANAMAN DI DUSUN GENDER, KRADENAN, KALIWUNGU, KABUPATEN SEMARANG - SRI MULYANI; UNNA RIA SAFITRI; DONNA SETIAWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The Covid-19 pandemi has a major impact on all aspects and sectors in people’s lives, especially in the economic sector. One of the UMKM in Dusun Gender that experienced the impact was a cement plant pot business. Marketing, which is usually carried out only through direct promotion from one person to another, must now be further developed. Currently the whole world has entered the digital era, where internet networks and computer information technology can be accessed everywhere. Social media is indeed very attractive to UMKM to develop their business. Social media has a very big influence, people are quicker to receive information via the internet. With easy and fast access, this is used by small UMKM entrepreneurs to be more courageous in promoting their products because the internet network is very wide and there are no time and area restrictions so that it becomes an effective marketing medium. With marketing through sosial media it has had significant results there have been several orders made from outside the village who know about this pot business through sosial media